Synthesis and Structural Characterization of Furan-2,5-dicarbonylbis(N,N-diethylthiourea) and its Dinuclear Cu(II) and Zn(II) Complexes - Dinh, Le Canh; Nhung, Nguyen Hong; Huy, Nguyen Hung; Thang, Pham Chien; Hoi, Bui Van (VNU Journal of Science: Natural Sciences and Technology; Vol 40 No 4DO - 10.25073/2588-1140/vnunst.5760, 2024)
The condensation reaction of furan-2,5-dicarbonyl dichloride and N , N -diethylthiourea gave rise to furan-2,5-dicarbonylbis( N , N -diethylthiourea), H 2 L . The composition and structural features of H 2 L were studied by spectroscopic methods as well as single-crystal X-ray diffraction. H 2 L readily reacted with 1 equivalent of CuCl 2 or ZnCl 2 in MeOH with the presence of the supporting base Et 3 N. Such reactions resulted in metal complexes, which were characterized by spectroscopic studies. The results indicated dinuclear neutral compounds [M 2 (L) 2 ] (M = Cu(II) or Zn(II)), in which L 2– anions resulting from the deprotonation of H 2 L bond to metal ions through ( S , O )-donor sets of the aroylthiourea moieties.